Abdel Krim : Emir of the Rif - Furneaux, Rupert (Rawalpindi Army Education Press, 1967)
At the end of the First World War, France had to terminate its conquest of Morocco. Despite its military superiority, France had to attack the determination of resistance in the Middle Atlas, the High Atlas and Anti-Atlas. Pushed to the tops of mountains and peaks, Moroccan resistants strove to fight to the end against the imperialist armies to preserve their freedom. The most famous of these Moroccan militants was the Emir AbdelKrim El-Khattabi in the Rif region.
Include Bibliography and Index.
Keywords: Morocco -- Abdel-Krim, 1882-1963 -- Statesmen -- Rif Revolt (1921-1926)